Pengembangan Media Pembelajaran Komik Digital Berbantuan Canva Pada Mata Pelajaran Bahasa Indonesia Kelas V (Jurnal Keluarga Sehat Sejahtera, 2026)
This study aims to evaluate the feasibility, practicality, and effectiveness of Canva-assisted digital comic learning media in the Indonesian language subject for grade V at SDN 064036 Teladan Timur. The method used is research and development with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The subjects in this study were 1 media expert and 1 material expert, 1 grade V teacher, and 22 grade V students. Data collection techniques were carried out through interviews, questionnaires, and tests, with data analysis using qualitative and quantitative approaches. The validation results showed that the developed media obtained a score of 92% from media experts with the category of "very feasible", and 80% from material experts with the category of "feasible". Practicality, the media obtained a score of 100% from educators and 95% from students, both of which were in the "very practical" category. In addition, the results of the analysis of learning outcome improvements showed an average N-gain value of 0.76 with the "high" category. The media effectiveness test also showed a percentage of 76% which was classified as "very effective". In conclusion, the digital comic learning media developed using Canva is feasible and practical to use in learning, and is effective in improving the learning outcomes of fifth grade students at SDN 064036 Teladan Timur.